If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4b + -5(-6b + -6) = -126 Reorder the terms: -4b + -5(-6 + -6b) = -126 -4b + (-6 * -5 + -6b * -5) = -126 -4b + (30 + 30b) = -126 Reorder the terms: 30 + -4b + 30b = -126 Combine like terms: -4b + 30b = 26b 30 + 26b = -126 Solving 30 + 26b = -126 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 26b = -126 + -30 Combine like terms: 30 + -30 = 0 0 + 26b = -126 + -30 26b = -126 + -30 Combine like terms: -126 + -30 = -156 26b = -156 Divide each side by '26'. b = -6 Simplifying b = -6
| -2[4f+6]=28 | | D=7(6-3) | | (1/4x)2=3.14(40-x/2x)2 | | 10.5x+49.76=-9.5+49.68 | | 3x+5y=825 | | 7.1-1.8=26.6 | | 5x-2=-2x+4 | | (2x+8)(2x-8)=0 | | 7.3-2.4=19.5 | | -(z+5)+(2z+1)=-3(z+1) | | 4(5z-1)-5(z+2)=13(z+1) | | (3x+10)= | | 60=6[4-2d] | | -y^2-4y=-5 | | 4(5z-1)-5(z+6)=12(z+1) | | (3x+10)(5x-52)= | | 2[3b+4]=44 | | 2(-x-2)= | | 36=3[10-2x] | | (x+5)+(x-3)= | | n^2+4n=-4 | | (-2a+5)+(-6a)=x | | a-7+3-4a= | | 5y-19=-25 | | 5(6z-1)-4(z+7)=20(z+1) | | 54=3[2-4x] | | 3x+5y=740 | | 5x^2+40=33x | | 3x+5y=745 | | 2(3a-4)=10 | | 2x^2-40x+50=0 | | 93=-6k-7(k-4) |